Patient-reported outcomes 12 years after localized prostate cancer treatment - Donovan, JL; Hamdy, FC; Lane, JA; Young, GJ; Metcalfe, C; Walsh, EI; Davis, M; Steuart-Feilding, T; Blazeby, JM; Avery, KNL; Martin, RM; Bollina, P; et al. (NEJM Group, 2023)

(untitled)
BACKGROUND Long-term patient-reported outcomes are needed to inform treatment decisions for localized prostate cancer. METHODS Patient-reported outcomes of 1643 randomly assigned participants in the ProtecT (Prostate Testing for Cancer and Treatment) trial were evaluated to assess the functional and quality-of-life impacts of prostatectomy, radiotherapy with neoadjuvant androgen deprivation, and active monitoring. This article focuses on the outcomes of the randomly assigned participants from 7 to 12 years using mixed effects linear and logistic models. RESULTS Response rates exceeded 80% for most measures. Among the randomized groups over 7 to 12 years, generic quality-of-life scores were similar. Among those in the prostatectomy group, urinary leakage requiring pads occurred in 18 to 24% of patients over 7 to 12 years, compared with 9 to 11% in the active monitoring group and 3 to 8% in the radiotherapy group. In the prostatectomy group, 18% reported erections sufficient for intercourse at 7 years, compared with 30% in the active monitoring and 27% in the radiotherapy groups; all converged to low levels of potency by year 12. Nocturia (voiding at least twice per night) occurred in 34% in the prostatectomy group compared with 48% in the radiotherapy group and 47% in the active monitoring group at 12 years. Fecal leakage affected 12% in the radiotherapy group compared with 6% in the other groups by year 12. The active monitoring group experienced gradual age-related declines in sexual and urinary function, avoiding radical treatment effects unless they changed management. CONCLUSIONS ProtecT provides robust evidence about continued impacts of treatments in the long term. These data allow patients newly diagnosed with localized prostate cancer and their clinicians to assess the trade-offs between treatment harms and benefits and enable better informed and prudent treatment decisions. (Funded by the UK National Institute for Health and Care Research Health Technology Assessment Programme projects 96/20/06 and 96/20/99; ISRCTN number, ISRCTN20141297; ClinicalTrials.gov number, NCT02044172.)